PROTECTIVE OVERLAYER TECHNIQUES FOR PREPARATION OF INSB(001) SURFACES - Evans, S; Cao, L; Egdell, R; Droopad, R; Parker, S; Stradling, R (1990)
A procedure has been developed for the preparation of clean, ordered InSb(001) surfaces outside epitaxial growth systems. This involves deposition of Sb caps onto freshly grown InSb(001) in a MBE system. The cap protects the underlying InSb from atmospheric contamination and can be removed subsequently from the InSb surface by thermal treatment alone to regenerate an ordered InSb(001) surface suitable for surface science experiments. HREELS measurement show that the carrier concentration at the surface of Si-doped InSb(001) (n+ = 1 × 1018 cm-3) prepared in this way is close to the bulk value. © 1990.